Socialization Of The Utilization Of Household Waste Into Valued Products In Tanjung Selamat Village - L. Lindawati; Sari Wardani; Dewi Maya Sari; A. Alaisyi; Ahmad Zamakhari (International Journal Of Community Service, 2022)
Waste is one of the common problems faced by the whole world, including Indonesia. Most of the national waste is generated from household activities. People still think that garbage is an object that has no value and must be thrown away. On the other hand, some of the waste can still be processed and reused. This service aims to provide knowledge to the community regarding the handling of household waste using the 3R principle. The target community in this service is the Housewivesin Tanjung Selamat Village. The method applied in this community service is education related to the types and dangers of waste and socialization of the reuse of household waste into products worth selling. The results of this activity indicate that the community is enthusiastic about taking part in the utilization of household waste into a viable product. This can open people's horizons to see entrepreneurial opportunities that can improve their economy. partners showed an increase in knowledge after participating in this activity.